2018
DOI: 10.1016/j.seppur.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

The application of pressure-driven ceramic membrane technology for the treatment of industrial wastewaters – A review

Abstract: This paper presents a review of the previous laboratory analysis and case studies on the application of the pressure-driven ceramic membrane technology for treatment of industrial wastewaters. Ceramic membranes has attracted remarkable interests in recent decades for industrial wastewater treatment because of their superior characteristic such as high fluxes , reliable working lifetime under aggressive operating conditions and ease of cleaning. The literature review revealed that the efficiency of this technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
82
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(99 citation statements)
references
References 214 publications
(214 reference statements)
0
82
0
3
Order By: Relevance
“…Ceramic membranes exhibit several advantages compared with polymeric membranes, including excellent mechanical and chemical stability, high pressure tolerance, suitability for a wide range of treatment environments, high flux, and long service life. [1][2][3][4][5] These superior characteristics make them preferable for the wastewater treatment, if it were not for the fact that they are of high cost. The primary materials for the fabrication of ceramic membranes include alumina, 6,7 titania, 8,9 zirconia, 5,10 silicon nitride, 11,12 and silicon carbide.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic membranes exhibit several advantages compared with polymeric membranes, including excellent mechanical and chemical stability, high pressure tolerance, suitability for a wide range of treatment environments, high flux, and long service life. [1][2][3][4][5] These superior characteristics make them preferable for the wastewater treatment, if it were not for the fact that they are of high cost. The primary materials for the fabrication of ceramic membranes include alumina, 6,7 titania, 8,9 zirconia, 5,10 silicon nitride, 11,12 and silicon carbide.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the microfiltration membranes are made from polymeric materials, but inorganic materials are also widely used. Ceramic membranes have become the favored option because of their extremely high chemical, mechanical and thermal stability, ease of cleaning and sterilization stability, their outstanding separation characteristics, and their long working life …”
Section: Introductionmentioning
confidence: 99%
“…Ceramic membranes have become the favored option because of their extremely high chemical, mechanical and thermal stability, ease of cleaning and sterilization stability, their outstanding separation characteristics, and their long working life. 12,13 During the cross-flow microfiltration of cultivation broths of different microorganisms, membrane fouling emerges as the major issue. 14,15 The main cause of microfiltration membrane fouling is deposition of cells, different organic substances present in cultivation broth, either as cultivation medium remains or as produced metabolites, on the membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, in the case of a dairy company that processes 1000 m 3 of milk per day, potential profits of USD 349,000 per year could be obtained. Ceramic membranes can also be successfully used for the treatment of industrial wastewater [11]. From the literature review made by Samaei et al, it can be concluded that the MF (microfiltration) and UF (ultrafiltration) ceramic membranes have gained much attention in the treatment of wastewater from the food industry owing to their higher durability compared with polymeric membranes [11].…”
mentioning
confidence: 99%
“…Ceramic membranes can also be successfully used for the treatment of industrial wastewater [11]. From the literature review made by Samaei et al, it can be concluded that the MF (microfiltration) and UF (ultrafiltration) ceramic membranes have gained much attention in the treatment of wastewater from the food industry owing to their higher durability compared with polymeric membranes [11]. Therefore, the development of effective industrial wastewater treatment technologies for reuse is one of the research priorities in the scientific communities [31].In view of the foregoing, the membrane fouling by confectionery wastewater has not been explored fully to-date, including the impact of pretreated photooxidation.…”
mentioning
confidence: 99%